REGIONAL MODEL OF SUSTAINABLE DEVELOPMENT AND AGENDA 21 - Romero B., Alfonso (2002)
The present article proposes a hypothesis for developing regions on a short term by means of performing an optimal management of regional governments, framed within a sustainable development model as weIl as Program 21 guidelines. Strengths, weaknesses and general suggestions for each aspect of the regional sustainable development model are highlighted.